Lecture series addresses ethics, the First Amendment and schools - Uribes, Tom::::::::: (2013)
Dr. Charles Haynes, director of the Religious Freedom Education Project at the Newseum and a senior scholar at the First Amendment Center at Vanderbilt University in Nashville, will participate in two panels at the Leon S. Peters Ethics Lecture Series, 'Civic Education, Religious Diversity, & Democracy,'